Edukasi Literasi Keuangan di Sekolah Dasar Negeri - Jaki Yudin; Dede Trisna Wijaya; Delis Lestia Nuratipa (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
Financial literacy in Indonesia, especially in rural areas, still needs to be improved. In Sindangkasih District, Majalengka, three elementary schools face challenges in teaching financial literacy to students. This community service program aims to instill an understanding of financial literacy and encourage creative practices for students to manage their finances. Financial literacy education is carried out through conventional methods, including three stages: planning, implementation, and monitoring and evaluation. The results of this activity show that students' understanding of money management reaches an average of more than 60%, and the frequency of students' saving activities is around twice a week. These findings indicate that students can gradually understand and apply financial literacy education, especially through routine savings habits.